## Results (displaying matches 1-50 of 3371) Next

Label Class Equation Sato-Tate $$\overline{\Q}$$-simple $$\GL_2$$ Rank*
336.a.172032.1 336.a $$y^2 + (x^3 + x)y = -x^6 + 15x^4 - 75x^2 - 56$$ $G_{3,3}$ 0
644.a.2576.1 644.a $$y^2 + (x^2 + x)y = -5x^6 + 11x^5 - 20x^4 + 20x^3 - 20x^2 + 11x - 5$$ $G_{3,3}$ 0
672.a.172032.1 672.a $$y^2 + (x^3 + x)y = -x^6 - 16x^4 - 75x^2 + 56$$ $G_{3,3}$ 0
676.b.17576.1 676.b $$y^2 + (x^2 + x)y = -x^6 + 3x^5 - 6x^4 + 6x^3 - 6x^2 + 3x - 1$$ $E_1$ 0
784.b.25088.1 784.b $$y^2 + (x^2 + 1)y = -x^6 - 3x^5 + 7x^4 + 2x^3 - 49x^2 + 41x - 9$$ $G_{3,3}$ 0
784.b.76832.1 784.b $$y^2 + (x + 1)y = -x^6 + 4x^5 - 4x^4 - 2x^3 + 10x - 9$$ $G_{3,3}$ 0
800.a.8000.1 800.a $$y^2 + (x^3 + x^2 + x + 1)y = -x^6 + 2x^4 + 4x^3 + 2x^2 - 1$$ $G_{3,3}$ 0
816.b.52224.1 816.b $$y^2 + (x^3 + x)y = -x^6 - 12x^4 - 27x^2 - 17$$ $G_{3,3}$ 0
847.d.847.1 847.d $$y^2 + (x^3 + x^2 + x + 1)y = -12x^6 - 15x^5 + 9x^4 + 31x^3 + 9x^2 - 15x - 12$$ $G_{3,3}$ 0
847.d.456533.1 847.d $$y^2 + y = -x^6 - 9x^5 - 22x^4 + 3x^3 + 37x^2 - 24x + 4$$ $G_{3,3}$ 0
936.a.1872.1 936.a $$y^2 + (x^3 + x)y = -x^6 - 9x^4 - 32x^2 - 39$$ $G_{3,3}$ 0
961.a.961.1 961.a $$y^2 + (x^3 + x + 1)y = -x^6 - x^5 - 7x^4 + 74x^3 - 145x^2 + 99x - 33$$ $G_{3,3}$ 0
961.a.961.2 961.a $$y^2 + (x^3 + x + 1)y = -x^6 + 2x^5 - 8x^4 + 12x^3 - 18x^2 + 12x - 7$$ $G_{3,3}$ 0
980.a.878080.1 980.a $$y^2 + (x^3 + 1)y = -x^6 + x^5 - 4x^4 + 2x^3 - 4x^2 + x - 1$$ $G_{3,3}$ 0
1050.a.131250.1 1050.a $$y^2 + (x^2 + x)y = 3x^6 + 8x^5 + 15x^4 + 17x^3 + 15x^2 + 8x + 3$$ $G_{3,3}$ 0
1083.b.87723.1 1083.b $$y^2 + y = -x^6 - 3x^5 - 8x^4 - 11x^3 - 14x^2 - 9x - 6$$ $G_{3,3}$ 0
1083.b.390963.1 1083.b $$y^2 + y = -x^6 + 3x^5 - 50x^4 + 95x^3 - 14x^2 - 33x - 6$$ $G_{3,3}$ 0
1104.b.141312.1 1104.b $$y^2 + (x^3 + x)y = -x^6 - 3x^4 + 29x^2 - 46$$ $G_{3,3}$ 0
1253.a.1253.1 1253.a $$y^2 + (x^3 + x^2 + 1)y = -x^6 + 2x^5 - 33x^3 + 43x^2 + 15x - 330$$ $\mathrm{USp}(4)$ 0
1269.b.102789.1 1269.b $$y^2 + (x^3 + x)y = -2x^6 - x^5 - 21x^4 - 8x^3 - 80x^2 - 16x - 103$$ $\mathrm{USp}(4)$ 0
1344.a.4032.1 1344.a $$y^2 + xy = -x^6 - 12x^4 - 48x^2 - 63$$ $N(G_{1,3})$ 0
1470.a.2940.1 1470.a $$y^2 + (x^2 + x)y = -x^6 + 2x^5 - 5x^4 + 4x^3 - 5x^2 + 2x - 1$$ $G_{3,3}$ 0
1564.a.50048.1 1564.a $$y^2 + (x^3 + 1)y = -x^6 + 7x^5 + 8x^4 + 17x^3 + 8x^2 + 7x - 1$$ $G_{3,3}$ 0
1680.a.16800.1 1680.a $$y^2 + (x^3 + x)y = -x^6 - 18x^4 - 136x^2 - 350$$ $G_{3,3}$ 0
1795.a.224375.1 1795.a $$y^2 + (x^3 + x^2 + x)y = -x^6 - 8x^4 + 3x^3 - 23x^2 + 6x - 23$$ $\mathrm{USp}(4)$ 0
1920.a.368640.1 1920.a $$y^2 + (x^3 + x^2 + x + 1)y = 5x^6 + 6x^5 + 17x^4 + 12x^3 + 17x^2 + 6x + 5$$ $G_{3,3}$ 0
1923.a.1923.1 1923.a $$y^2 + (x^3 + x + 1)y = -x^6 + x^5 - 3x^4 + 2x^3 - 3x^2 + x - 1$$ $\mathrm{USp}(4)$ 0
1988.a.3976.1 1988.a $$y^2 + (x^2 + x)y = 6x^6 + 16x^5 + 31x^4 + 35x^3 + 31x^2 + 16x + 6$$ $G_{3,3}$ 0
2016.a.4032.1 2016.a $$y^2 + y = -2x^6 - 6x^5 - 10x^4 - 10x^3 - 7x^2 - 3x - 1$$ $G_{3,3}$ 0
2058.a.2058.1 2058.a $$y^2 + (x^3 + 1)y = 5x^6 - 4x^5 - 5x^4 + 14x^3 - 5x^2 - 4x + 5$$ $N(G_{1,3})$ 0
2058.a.16464.1 2058.a $$y^2 + (x^3 + 1)y = -3x^6 + 5x^5 - 11x^4 + 10x^3 - 11x^2 + 5x - 3$$ $N(G_{1,3})$ 0
2178.a.13068.1 2178.a $$y^2 + (x^3 + 1)y = -x^6 - x^4 - x^2 - 1$$ $G_{3,3}$ 0
2178.b.287496.1 2178.b $$y^2 + (x^2 + x)y = -x^6 - 2x^5 + 3x^4 - 8x^2 + 9x - 3$$ $G_{3,3}$ 0
2208.a.141312.1 2208.a $$y^2 + (x^3 + x)y = -x^6 + 2x^4 + 29x^2 + 46$$ $G_{3,3}$ 0
2304.b.147456.1 2304.b $$y^2 = -x^6 - 2x^4 - 2x^2 - 1$$ $E_1$ 0
2312.c.591872.1 2312.c $$y^2 + xy = -32x^6 - 31x^4 - 10x^2 - 1$$ $G_{3,3}$ 0
2380.a.33320.1 2380.a $$y^2 + (x^2 + x)y = -14x^6 + 26x^5 - 56x^4 + 53x^3 - 56x^2 + 26x - 14$$ $G_{3,3}$ 0
2484.a.9936.1 2484.a $$y^2 + (x^3 + x)y = -x^6 - 8x^4 - 24x^2 - 23$$ $N(G_{1,3})$ 0
2500.a.400000.1 2500.a $$y^2 + (x^3 + 1)y = -2x^6 - 2x^5 + 2x^3 - 2x - 2$$ $J(E_1)$ 0
2520.c.680400.1 2520.c $$y^2 + (x^2 + 1)y = -75x^6 - 65x^4 - 19x^2 - 2$$ $G_{3,3}$ 0
2640.a.2640.1 2640.a $$y^2 + (x^3 + x)y = -x^6 - 10x^4 - 40x^2 - 55$$ $G_{3,3}$ 0
2688.a.172032.1 2688.a $$y^2 + y = -12x^6 - 36x^5 - 61x^4 - 62x^3 - 42x^2 - 17x - 4$$ $G_{3,3}$ 0
2730.a.13650.1 2730.a $$y^2 + (x^3 + 1)y = -x^6 - 5x^5 + 3x^4 + 56x^3 - 7x^2 - 195x + 131$$ $G_{3,3}$ 0
2872.a.367616.1 2872.a $$y^2 + xy = -8x^6 - 28x^5 - 65x^4 - 88x^3 - 88x^2 - 51x - 20$$ $\mathrm{USp}(4)$ 1
2890.b.49130.1 2890.b $$y^2 + (x^3 + 1)y = -x^6 + 5x^5 - 9x^4 + 4x^3 - 9x^2 + 5x - 1$$ $G_{3,3}$ 0
2955.a.2955.1 2955.a $$y^2 + (x^3 + x)y = -x^6 - x^4 - x^3 - 3x^2 - 2x - 1$$ $\mathrm{USp}(4)$ 0
3012.a.6024.1 3012.a $$y^2 + (x^3 + x + 1)y = -x^6 + 2x^5 - 4x^4 + 3x^3 - 3x^2 + x - 1$$ $\mathrm{USp}(4)$ 0
3072.a.196608.1 3072.a $$y^2 = -2x^6 - 9x^4 - 13x^2 - 6$$ $N(G_{1,3})$ 0
3072.b.196608.2 3072.b $$y^2 = 2x^6 + 9x^4 + 13x^2 + 6$$ $N(G_{1,3})$ 0
3120.b.199680.1 3120.b $$y^2 + xy = -80x^6 - 189x^4 - 149x^2 - 39$$ $G_{3,3}$ 0
Next